Effect of bandpass filter bandwidth on the performance of linear cavity multiwavelength BEFL - A., Mansoor (IEEE, 2015)
We have investigated the self-lasing effect of the linear multiwavelength Brillouin-Erbium fiber laser with different tunable bandpass filter's bandwidth. Two 3dB bandwidth of 1 nm and 3 nm filter were used in this study. The experimental results show that the width of the TBF bandwidth plays an important role in shaping the self-lasing effect. By using the tunable bandpass filter with a broader bandwidth, the self-lasing effect can be suppressed efficiently thus producing higher Brillouin Stokes lines. At 0 dBm Brillouin pump power, up to 11 stable output laser channels can be obtained with the utilization of the 3 nm TBF as compared to only 5 output channels with the utilization of 1 nm TBF. © 2013 IEEE.